Docking Characterization and in vitro Inhibitory Activity of Flavan-3-ols and Dimeric Proanthocyanidins Against the Main Protease Activity of SARS-Cov-2 - Zhu, Yue; Xie, De-Yu (Frontiers in Plant Science, 2020)
We report to use the main protease (Mpro) of SARS-Cov-2 to screen plant flavan-3-ols and proanthocyanidins. Twelve compounds, (-)-afzelechin (AF), (-)-epiafzelechin (EAF), (+)-catechin (CA), (-)-epicatechin (EC), (+)-gallocatechin (GC), (-)-epigallocatechin (EGC), (+)-catechin-3-O-gallate (CAG), (-)-epicatechin-3-O-gallate (ECG), (-)-gallocatechin-3-O-gallate (GCG), (-)-epigallocatechin-3-O-gallate (EGCG), procyanidin A2 (PA2), and procyanidin B2 (PB2), were selected for docking simulation. The resulting data predicted that all 12 metabolites could bind to Mpro. The affinity scores of PA2 and PB2 were predicted to be -9.2, followed by ECG, GCG, EGCG and CAG, -8.3 to -8.7, and then six flavan-3-ol aglycones, -7.0 to -7.7. Docking characterization predicted that these compounds bound to three or four subsites (S1, S1’, S2, and S4) in the binding pocket of Mpro via different spatial ways and various formation of one to four hydrogen bonds. In vitro analysis with 10 available compounds showed that CAG, ECG, GCG, EGCG, and PB2 inhibited the Mpro activity with an IC50 value, 2.98±0.21, 5.21±0.5, 6.38±0.5, 7.51±0.21, and 75.3±1.29 µM, respectively, while CA, EC, EGC, GC, and PA2 did not have inhibitory activities. To further substantiate the inhibitory activities, extracts prepared from green tea (GT), two muscadine grapes (MG), cacao, and dark chocolate (DC), which are rich in CAG, ECG, GAG, EGCG or/and PB2, were used for inhibitory assay. The resulting data showed that GT, two MG, cacao, and DC extracts inhibited the Mpro activity with an IC50 value, 2.84 ±0.25, 29.54 ±0.41, 29.93±0.83, 153.3±47.3, and 256.39 ±66.3 µg/ml, respectively. These findings indicate that on the one hand, the structural features of flavan-3-ols are closely associated with the affinity scores; on the other hand, the galloylation and oligomeric types of flavan-3-ols are critical in creating the inhibitory activity against the Mpro activity.